Instrument Development of Science Literacy Assessment with Socio-Sciences Contains in Natural Science Learning for Elementary School (Journal of Research and Educational Research Evaluation, 2022)
The preparation of test instruments based on scientific literacy was one of the efforts to measure students' literacy skills, especially in the field of science or science. The aim of this study was to produce a scientific literacy assessment instrument containing socio-sciences in primary school science learning with the theme of heat and its displacement. The research method used in this study was the research and development method or often referred to as 4D (Define, Design, Development, Dissemination) by simplifying the stages of development into 3D (Define, Design, Development). The results showed that the average value of the instrument content validity was 85.03% which was declared very valid and the empirical validity value was 80.00%. The results of the practicality test of the scientific literacy assessment instrument containing socio-sciences by the teacher obtained a score of 89.52% and by students 88.43%. The reliability of the scientific literacy assessment instrument containing socio-sciences shows a high category with a reliability value of 0.83, there are 80% of questions with moderate difficulty criteria, and 66% of questions with good discriminating power. Based on the results of the research, it can be concluded that the scientific literacy assessment instrument containing socio-sciences of heat material and its transfer can be declared valid, practical, and reliable.